Straw and forage production of annual and perennial species in succession to soybean - Machado, Luís Armando Zago; Assis, Paulo Giovani Gall de (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate forage and straw production, of annual and perennial forage implanted in succession to soybean, and their effects on crop grain yield in the following season. The experimental design was in randomized blocks with four replicates, in a split-plot arrangement (free growth and successive cuts). Eight forages were evaluated in two municipalities of the state of Mato Grosso do Sul, Brazil. Straw and forage production was evaluated in 2005 and 2006, in the following species: Urochloa ruziziensis, U. decumbens; U. brizantha cv. Marandu and Xaraés; Panicum maximum cv. Tanzânia and Mombaça, P. maximum x P. infestans cv. Massai, Pennisetum americanum cv. BRS 1501, and Sorghum bicolor cv. Santa Elisa. Forages were planted mechanically, after the soybean crop harvest on 4/1/2005 and 3/24/2006, in São Gabriel do Oeste, and 3/20/2005 and 3/13/2006, in Dourados. Sorghum, U. brizantha cv. Xaraés and P. maximum cv. Tanzânia characteristics, such as high productivity, high forage quality and easiness in control, were favorable for production of both forage and straw. Urochloa ruziziensis and U. decumbens showed better performance for straw production. Forage cultivation in soybean succession does not affect crop yield.
Keywords: Panicum; Urochloa; integrated crop-livestock; pearl millet; cover crop; no tillage